Strategy of developing nucleic acid-based universal monkeypox vaccine candidates - Papukashvili, Dimitri; Rcheulishvili, Nino; Liu, Cong; Wang, Xingyun; He, Yunjiao; Wang, Peng George (Frontiers in Immunology, 2022)
Until May 2022, zoonotic infectious disease monkeypox (MPX) caused by the monkeypox virus (MPXV) was one of the forgotten viruses considered to be geographically limited in African countries even though few cases outside of Africa were identified. Central and West African countries are known to be endemic for MPXV. However, since the number of human MPX cases has rapidly increased outside of Africa the global interest to this virus has markedly grown. The majority of infected people with MPXV have never been vaccinated against smallpox virus. Noteworthily, the MPXV spreads fast in men who have sex with men (MSM). Preventive measures against MPXV are essential to be taken, indeed, vaccination is the key. Due to the antigenic similarities, the smallpox vaccine is efficient against MPXV. Nevertheless, there is no specific MPXV vaccine until now. Nucleic acid vaccines deserve special attention since the emergency approval of two messenger RNA (mRNA)-based coronavirus disease 2019 (COVID-19) vaccines in 2020. This milestone in vaccinology has opened a new platform for developing more mRNA- or DNA-based vaccines. Certainly, this type of vaccine has a number of advantages including time- and cost-effectiveness over conventional vaccines. The platform of nucleic acid-based vaccines gives humankind a huge opportunity. Ultimately, there is a strong need for developing a universal vaccine against MPXV. This review will shed the light on the strategies for developing nucleic acid vaccines against MPXV in a timely manner. Consequently, developing nucleic acid-based vaccines may alleviate the global threat against MPXV.